Vulnerable child syndrome in the neonatal intensive care unit: A review and a new preventative intervention with feasibility and parental satisfaction data. (March 2021) - Hoge, Margaret K.; Heyne, Elizabeth; Nicholson, Theresa De Freitas; Acosta, Dailyn; Mir, Imran; Brown, L. Steven; Shaw, Richard J.; Chalak, Lina; Heyne, Roy
Abstract: Vulnerable Child Syndrome (VCS) occurs in the setting in which a child recovers from a life-threatening illness, as result of which the parent develops heightened parental perceptions of child vulnerability (PPCV). This leads to a pattern of overprotective parenting which may result in adverse neurodevelopmental and behavioral outcomes in the child over time. Parents of premature infants have been shown to be at increased risk of developing raised PPCV while their infants may develop symptoms of VCS. The PreVNT trial is a randomized controlled trial designed to test the efficacy of a 5-session manualized Cognitive Behavioral Therapy (CBT) intervention to reduce PPCV. Results of a pilot study of parents of premature infants ( n = 41) demonstrate that the intervention can be delivered with high ratings of treatment fidelity and with a completion rate of 100% during the NICU admission, and 78% at 6 months post term. Ratings of parental satisfaction ranged between 4.9 and 5 out of 5 demonstrating high satisfaction with the intervention. Pilot feasibility and maternal satisfaction data are presented for a group of 22 intervention families, which suggest a CBT model for understanding VCS is feasible and deemed helpful by parents. This review is gauged to summarize risk of VCS development, diagnosis of VCS, and effective treatments for VCS through Cognitive Behavioral Therapy. We also present a paradigm shift in a therapeutic approach by introducing the PreVNT Trial. Given that VCS can interfere with the long-term outcomes of both infant and family, it is important to understand VCS and address its involvement in NICU and post NICU discharge care. Further research is needed in this area.